THE INVOLVEMENT OF SUPPORTING STAFF IN THE MBKM PROGRAM AT UNIVERSITAS ISLAM MALANG - Sonny Elfiyanto; Ifit Novita Sari; Dwi Fita Heriyawati (Universitas Negeri Malang, 2022)
Abstract: This study aims to investigate the involvement of supporting staffs at the Universitas Islam Malang about the Merdeka Belajar Kampus Merdeka (MBKM). Supporting staff is an essential factor in improving the implementation of the MBKM program. Their involvement is beneficial for lecturers and students participating in this program. The supporting staff realized that this program impacted the development of their institution. There were 328 who participated in filling in the questionnaire, and 37 staffs were voluntary to be interviewed. The data collection was carried out by filling out questionnaires and supported by structured interviews to explore their answers in the questionnaire. From the data collection results, the supporting staff wanted to be more involved in the MBKM program. Moreover, through this program, they believed that the performance indicators of the Universitas Islam Malang can be increased and will improve their welfare if this program is successful. Also, they hope that this program can be developed well if they are involved in a sustainable workshop or seminar related to the MBKM program).Keywords: involvement, supporting staff, MBKM